Guanosine tetraphosphate (ppGpp) dependence of the growth rate control of rrnB P1 promoter activity in Escherichia coli. - V. James Hernandez; H. J. Bremer (1990)
This studyThis study ' JC9387 was transformed with linearized pVJH26 (Table I, cleaved with restriction endonuclease PstI) and selected for KanR.* JC9387 was transformed with linearized pVJH27 (Table I, as above) and selected for KanR.' MC4100 was transduced to Kans with a lysate of phage Pl grown on VH270.d VH271 was transduced to TetR with a lysate of phage Pl grown on CF930, screened for co-transduction of the